(untitled) (Biological Sciences - PJSIR, 2002)
The effect of humic acids (ammonium humate) derived from Pakistani lignite on the growth and grain yield of wheat (I’rzticum aeshvum-V) crop m the presence and absence of phosphate fertilizer and in combination with various levels of phsphate fertilizer was studied. Application of humic acids in all doses when applied alone and in combination with vanous levels of phosphate fertilizer (TSP) has significant beneficial effect on the growth and yield of wheat. An enhanced effect on the growth and grain yield was notified when Humic acids was added alone without using any fertilizer.